Log in to add a comment

Log in to add a comment

**Solution:**

3x2² - x - 2 = 0

Break the equation

⟹ 3x2^2 - 3x + 2x - 2 = 0

⟹ 3x(x - 1) + 2(x - 1) = 0

⟹ (x - 1)(3x + 2) = 0

To get the answer we have to use the zero-product rule

x - 1 = 0 or, 3x + 2 = 0

⟹ x = 1 or x = -2/3

Simplify the equation

x = -2/3, 1.

**3x2****² - x - 2 = 0**

**⟹ 3x2**²** - 3x + 2x - 2 = 0**

**⟹ 3x(x - 1) + 2(x - 1) = 0**

**⟹ (x - 1)(3x + 2) = 0**

**x - 1 = 0 or, 3x + 2 = 0**

** We get,**

**⟹ x = 1 or x = -****2/3**

**∴ Values of x = -****2/3, 1**